Direct evidence of coupling between charge density wave and Kondo lattice in ferromagnet Fe5GeTe2 - Parry Pei-Rui Luo; Hung-Chang Hsu; Li-Sheng Lin; Hao-Yu Chen; Xiang-Yu Xie; Chia-Nung Kuo; Jyh-Pin Chou; Chin-Shan Lue; Ya-Ping Chiu (Nature Communications)
Abstract d-electronic heavy fermion systems have sparked interest in exploring the connection between electronic and spin degrees of freedom in Kondo systems. Nevertheless, the coexistence of charge order on a Kondo lattice has yet to be discovered. Fe5GeTe2, a two-dimensional ferromagnet, intriguingly provides a promising avenue to bridge the gap, as this d-electronic Kondo system facilitates the ordering of charge and magnetic behaviors due to the influence of itinerant magnetism on local electronic band structure. Here, we present direct evidence for the coherent interplay between Kondo interaction and charge density wave (CDW) phenomena in Fe5GeTe2 using scanning tunneling microscopy/spectroscopy (STM/STS). From the electronic structure, we observe a $$\sqrt{3}× \sqrt{3}{R}30^°$$ 3 × 3 R 3 0 ∘ modulation accompanied by phase inversion, indicative of CDW. Concurrently, the presence of a Fano-like peak near the Fermi level corroborates the Kondo lattice behavior. Furthermore, formations of Kondo holes at defect sites underscore the influence of Kondo interaction on local electronic structures. To unveil the robust correlation between CDW and Kondo lattice behavior, we analyze the CDW modulation and develop a theoretical model to interpret their robust coupling. Our findings advance the understanding of Kondo physics in d-electronic ferromagnetic systems and highlight Fe5GeTe2 as a promising platform for exploring low-dimensional magnetism.